The Incidence of Euphoria in Multiple Sclerosis: Artefact of Measure. (13th June 2016) - Duncan, Amy; Malcolm-Smith, Susan; Ameen, Ozayr; Solms, Mark
Abstract : Background . A subgroup of MS patients present with "euphoria." Classical authors describe this symptom as the predominant mood state of these patients, while contemporary authors regard it as rare. Objective . This study aimed to address these discrepancies and investigate the contributions made by varying operational definitions and measurement instruments. Methods . One hundred MS patients and 100 matched controls completed the classical interview of Cottrell and Wilson and the modern Neuropsychiatric Inventory in a once-off interview. Results . The MS group demonstrated high frequencies of euphoria using the classical measure but low frequencies using the contemporary measure and definition. The matched control group demonstrated significantly higher rates than the MS group using the classical measure and lower rates than the MS group using the contemporary measure. Conclusion . The discrepancies in incidence rates of euphoria noted in the literature do not reflect a change in the incidence of euphoria in MS, but rather in the definition and operationalisation of "euphoria." Furthermore, these results highlight the importance of characterising what represents pathological euphoria as well as the need for better definitions and instruments of measure.